Meditation Effective in Reducing Teacher Burnout and Improving Resilience: A Randomized Controlled Study - Valosek, Laurent; Wendt, Staci; Link, Jan; Abrams, Allan; Hipps, Jerry; Grant, James; Nidich, Randi; Loiselle, Marie; Nidich, Sanford (Frontiers in Education, 2021)
Teacher burnout affects job performance and mental and physical health. This study evaluated the effects of a meditation-based wellness program on burnout, resilience, psychological distress, and fatigue. Seventy-eight participants, randomly assigned to the Transcendental Meditation program (n = 39) or to a wait-list control group (n = 39), were administered the Maslach Burnout Inventory, Resilience Scale, Perceived Stress Scale, and the National Institutes of Health Patient-Reported Outcomes Measurement Information System fatigue and depression scales at baseline and at four-month posttest. Intention-to-treat with all 78 participants was used for all analyses. Significant reduction on emotional exhaustion, the main scale of the Maslach Burnout Inventory, was found for the meditation group compared to controls (p = 0.019). Significant improvements were also found on resilience (p = 0.014), perceived stress (p < 0.001), fatigue (p = 0.001), and depression (p = 0.091). Eighty-seven percent were compliant with their meditation home practice. Findings indicate that meditation is effective in improving burnout and associated resilience, psychological distress, and fatigue factors. Teachers may benefit from in-school wellness programs.